Transverse polarization measurement of Λ hyperons in pNe collisions at √sNN = 68.4 GeV with the LHCb detector - Aaij, Roel; Bachmann, Sebastian; Carus, Leon; Caspary, Rowina; Celani, Sara; Cocha Toapaxi, Carlos; De Cian, Michel; Dittmann, Lucas; Esen, Sevda; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Journal of high energy physics, 2024)
A measurement of the transverse polarization of the Λ andΛ hyperons in pNe fixed-target collisions at √sNN = 68.4 GeV is presented using data collected by the LHCb detector. The polarization is studied using the decay Λ → pπ− together with its charge conjugated process, the integrated values measured are PΛ = 0.029 ± 0.019 (stat) ± 0.012 (syst), PΛ = 0.003 ± 0.023 (stat) ± 0.014 (syst). Furthermore, the results are shown as a function of the Feynman x variable, transverse momentum, pseudorapidity and rapidity of the hyperons, and are compared with previous measurements.
*The LHCb collaboration: R. Aaij, S. Bachmann, L. Carus, R. Caspary, S. Celani, C. Cocha Toapaxi, M. De Cian, L. Dittmann, S. Esen, P.A. Günther, X. Han, S. Hansmann-Menzemer, P. Herrero Gascon, C. Langenbruch, B. Leverington, J. Marks, M.P. Morgenthaler, S.R. Roy, M. Ruiz Diaz, G. Tuci, L.H. Uecker, D.J. Unverzagt, U. Uwer, L. Witola, Y. Zhao, A. Zhelezov [und sehr viele weitere Personen]
Gesehen am 10.09.2025
Im Titel steht der Ausdruck "sNN" unter dem Wurzelsymbol